THE IMPORTANCE OF PHYSICAL TRAINING IN THE UPBRINGING OF THE MORAL NORMS, WILLPOWER AND OTHER CHARACTERISTICS OF THE STUDENT (Spectrum Journal of Innovation, Reforms and Development, 2023)
In this article, the general education school consists in providing instructions on the moral education of students and will and other qualities of students, formed depending on physical activity.